PENGARUH PEMBELAJARAN PENDIDIKAN KEWARGANEGARAAN SEBAGAI PENDIDIKAN DEMOKRASI TERHADAP CIVIC RESPONSIBILITY PADA MAHASISWA - Nurul Febrianti; Cecep Darmawan (Program Studi PPKn FIS UNJ & Asosiasi Profesi PPKn Indonesia, 2016)
This study reviewss (1) Influence of learning materials for civics on the civic responsibility of student, (2) Influence of learning methods for civics on the civic responsibility of the student, (3) Influence of instructional media for civics on the civic responsibility of the student.The research uses a quantitative approach with survey method. Data collection using the study questionnaire. The population in this study is the Jakarta State University student who contracted general courses in the second semester Citizenship Education (102) in 2015. The results showed that (1) Learning materials Civics significant influence on civic responsibility in students with t count 6,502 > t table 1.971. (2) Methods of teaching Civics significant influence on civic responsibility in students with t count 7.290 > t table 1.971. (3) Media Learning Civics significant influence on civic responsibility in students with t count 3.737 > t table 1.971.